2020
DOI: 10.1039/d0nj01041c
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch synthesis using a cobalt catalyst supported on graphitic carbon nitride

Abstract: The nitrogen atoms in a g-C3N4 support improved cobalt reduction in a prepared Co/g-C3N4 catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…They also found that with the increase in the size of the cobalt cluster, the rate of chain growth increases. In the previous work, 53 cobalt particles of different sizes were prepared by using different supports in the FTS reaction. The results showed that with the increase in the size of the cobalt particles, the chain growth increases.…”
Section: Resultsmentioning
confidence: 99%
“…They also found that with the increase in the size of the cobalt cluster, the rate of chain growth increases. In the previous work, 53 cobalt particles of different sizes were prepared by using different supports in the FTS reaction. The results showed that with the increase in the size of the cobalt particles, the chain growth increases.…”
Section: Resultsmentioning
confidence: 99%
“…g‐C 3 N 4 was produced through the procedure in literature by using melamine 47 . To obtain a graphitic carbon nitride nanosheet, 30 g of melamine was kept in an electric furnace and heated at 550°C for 2 h.…”
Section: Methodsmentioning
confidence: 99%
“…4 Therefore, in most cases Fe and Co are used in the industry. 2,5 Although Co is more expensive than Fe, it has a high selectivity to paraffins and low selectivity to olefins and oxygenated compounds, and therefore, Co is the preferred choice to produce long chain paraffins, 6 while Fe is a better choice to generate olefins. 4 Iron-based catalysts are more desirable than Co-based catalysts, especially for coal- or biomass-derived syngas with lower H 2 /CO ratios.…”
Section: Introductionmentioning
confidence: 99%